(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Air pollution is one of the most dangerous and important problems in the world and a source of great concern for many developing and developed countries, especially in urban areas. Given its impact on the environment and human, animal and plant health, the current article provides a brief review of air pollution, and the effect of plants as a bio remedial agent to get rid of air pollutants. And the heavy elements found in the soil and the most important plants that resist pollution. The cause of air and soil pollution may be due to the increase in population growth, the high rate of industry, and the absence of adequate planning and environmental awareness related to development, development, and consumption. These factors contribute to the increase in the percentage of pollution.